Effects of protecting broccoli plants with nonwoven polypropyleno - Santos, G. M. [UNESP]; Braz, L. T. [UNESP]; Grilli, G. V G [UNESP]; Costa, C. C. [UNESP] (My University, 2003)
This investigation was conducted between June and September, in an experimental area, whose coordinates are latitude 21°15'22 south and longitude 48°18'58 east, situated at a mean altitude of 575 m. The soil of the area is classified as Red Latossolo (Commission of Soils, 1960), Haplorthox soil. The effects of two cultivation systems: protection with nonwoven polypropyleno and in an open field, on broccoli cultivars 'Baron', 'Shigimori', 'Pinacco' were evaluated. The experiments were a randomized block experimental design, using a factorial arrangement of 3 (cultivars) x 2 (cultivation systems), with four replicates. The characteristics evaluated were precociousness, longitudinal and transverse diameters of broccoli heads, fresh mass of broccoli heads and number of leaves per plant. The 'Baron' cultivar was more precocious, having its harvest at 86 days after transplanting in both cultivation systems. 'Baron', despite being more precocious, had inferior results in relation to the other cultivars. The open field cultivation system was optimum for cultivars 'Shigimori' and 'Pinacco'.
Keywords: Brassica oleracea var. italica; Cultivation system; Productivity